Impact of different antiplatelet therapy cessation modes on outcomes in patients treated with ticagrelor with or without aspirin after PCI: the twilight-antiplatelet cessation study. (3rd October 2022) - Spirito, A; Kastrati, A; Moliterno, D J; Baber, U; Cao, D; Sartori, S; Collier, T; Gibson, C M; Angiolillo, D J; Pocock, S J; Cohen, D J; Escaned, J; et al.
Abstract: Background: The Ticagrelor With Aspirin or Alone in High-Risk Patients After Coronary Intervention (TWILIGHT) trial showed that a regimen consisting of a 3-month dual antiplatelet therapy (DAPT) followed by ticagrelor monotherapy reduces the rate of bleeding events without increasing ischemic complications compared with standard DAPT [1]. Previous studies, such as Patterns of Non-Adherence to Anti-Platelet Regimens in Stented Patients (PARIS) demonstrated how deviation or cessation of the prescribed antiplatelet regimen might negatively affect clinical outcomes [2]. Purpose: The proposed analysis aims to assess the impact of different antiplatelet therapy cessation patterns on ischemic and bleeding outcomes in patients treated with ticagrelor with or without aspirin after percutaneous coronary intervention (PCI). Methods: All 7, 119 patients randomized at 3 months post-PCI in the TWILIGHT study will be included. The analyses will be conducted separately in the two treatment arms (ticagrelor plus placebo and ticagrelor plus aspirin). According to the PARIS study definitions and as prespecified in the TWILIGHT trial protocol, the occurrence of the three following antiplatelet cessation modes will be assessed: 1) discontinuation (e.g., caused by intolerable side effects or because of a safety concern); 2) interruption (temporary, <14 days, because of surgical or other invasive procedures); 3) disruption (due to non-compliance or bleeding). The primary endpoint will be the composite of all-cause death, myocardial infarction (MI), or stroke at 12 months after randomization. The key secondary endpoint will be BARC type 2, 3 or 5 bleeding. Other secondary endpoints will include the components of the primary endpoint, cardiovascular death, definite or probable stent thrombosis and BARC types 3 or 5 bleeding. The number of events will be estimated according to the antiplatelet cessation status before the clinical event. Hazard ratios and 95% confidence intervals will be generated using Cox proportional hazards models including antiplatelet therapy cessation as a time-updated variable. If more than one cessation event occurred during follow-up, the antiplatelet therapy cessation category will change only if the more recent mode is worse than the previous: disruption will have priority over interruption, which in turn will have priority over discontinuation. Patients without cessation events will represent the reference group. All adverse events and episodes of antiplatelet cessation were independently adjudicated. Results: The results of this analysis will be presented for the first time at ESC 2022. Conclusion: This prespecified analysis of the TWILIGHT study will show for the first time the impact on clinical outcomes of different antiplatelet therapy cessation modes when a regimen of Ticagrelor with our without aspirin is prescribed after PCI. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Astra Zeneca, United Kingdom